Normal pancreatic volume assessment using abdominal computed tomography volumetry. Issue 34 (27th August 2021) - Li, Lu; Wang, Shuang; Wang, Fei; Huang, Guo-ning; Zhang, Dong; Wang, Guang-xian
Abstract : Abstract: To determine the normal range of pancreatic volume (PV) in Chinese adults using computed tomography (CT) volumetry. To assess the relationships of PV with patient demographics and clinical parameters. To analyze the degree of correlation between PV values determined by manual segmentation and those calculated by formulas. A total of 240 adults (120 women, 120 men) between the ages of 18 and 79 years were reviewed. There were 6 groups of patients, with 40 patients in each decade regarding age. PV was segmented manually on computed tomography images slice by slice for each patient, and 2 formulas were used to calculate PV * and PV # . The mean PV was 77.44 ± 19.11 cm 3 (range from 28.55–138.15 cm 3 ). PV was significantly correlated with height ( r  = 0.427, P  < .001), weight ( r  = 0.525, P  < .001), body mass index ( r  = 0.377, P  < .001), the width of the first lumbar vertebral body ( r  = 0.166, P  = .01), the transverse abdominal diameter ( r  = 0.455, P  < .001), and the sagittal abdominal diameter ( r  = 0.456, P  < .001). There was a negative correlation between PV and age ( r  = –0.209, P  = .001). The correlation coefficients between PV and PV * and PV # were 0.676 and 0.376, respectively, with both P  < .001. PV associated with patient demographics and clinical parameters. A more accurate and simpler formula should be used in the future to calculate and monitor changes in PV.